2020
DOI: 10.1515/hf-2019-0180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extractives on mechanical properties and durability of rubberwood-HDPE composites

Abstract: In this study, the effects of rubberwood extractives on the mechanical properties and fungal decay resistance of rubberwood-based wood plastic composites (WPCs) were explored. Three different solvents, benzene-ethanol, methanol, and deionized water, were used to remove the extractives of the rubberwood flour (RWF). The surface topographies of the prepared rubberwood-based WPC and the rubberwood itself were characterized using digital instruments and scanning electron microscopy (SEM). The results indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…As a building component, WPC can be reinforced with FRP to improve its flexural performance [ 95 ]. Wang et al [ 96 ] studied the effects of bakelite extract on mechanical properties and anti-fungal corrosion of bakelite based WPMC. The results showed that the mechanical properties of xylan prepared with extracted RWF were higher than those of unextracted xylan.…”
Section: Other Methodsmentioning
confidence: 99%
“…As a building component, WPC can be reinforced with FRP to improve its flexural performance [ 95 ]. Wang et al [ 96 ] studied the effects of bakelite extract on mechanical properties and anti-fungal corrosion of bakelite based WPMC. The results showed that the mechanical properties of xylan prepared with extracted RWF were higher than those of unextracted xylan.…”
Section: Other Methodsmentioning
confidence: 99%